Incongruencias y dificultades en las respuestas de Políticas Públicas frente a los procesos de desplazamiento Interno en Colombia - Varela Barrios, Edgar (Cuadernos de Administración, 2003)
In Colombia, as it is know the forced migration process generated by differ ents sorts of violence which devastate society has increased in recent times. It is estimate that in the last three years more than two millions and a half people have been active subjets of displacement and forced migration. The associated causes to this phenomenon come from economics crashes in wide geographical areas to retaliations and threats coming from the diverse armed confict actors. This displacement has generated strong stress for the territorial entities (i.e. departments and department governors, municipalities and local governments). In this sense, it has been intended to built an external public policy to solve the problem which has been determinated by the rol that multilateral organizations such as, International Migration Organization I MO and NGOs play. This paper analize the response process implemented in the lastfour years and the creativity generated to find out alternatives to the present problems related to migrations andforced displacement treatment particularly in Colombian southwest area. It considers the international actors, the NGOs, the local and national goverment and the implicit dynamic of the so called "Plan Colombia", flghtind mechanism against drugs supported by the militar and economic aid from de United State to Columbia, started in Pastrana administrations and continued in President Alvaro Uribe goverment.